FENOMENA SIMBOLIK KESURUPAN DALAM PEMENTASAN TARI KUDA LUMPING SEBAGAI SIMBOL COUNTER HEGEMONI IDEOLOGI AGAMA - Mahattama Banteng Sukarno (SAGACITY : Journal of Theology and Christian Education, 2020)
The phenomenon of possession in the horse dance becomes a problematic issue in Javanese society. Negative stigmatization as a result of social action that maintains ideological hegemony has opened up a crisis room in Javanese society, especially Javanese Abangan. This study examines how the phenomenon of being possessed as a symbol of as an act of counter hegemony Ideology is carried out through the symbol of being possessed in the art of horse dance. Mircea eliade’s perspective on symbol and Antonio Gramci’s paradigm of ideological hegemony becomes the main analytical framework in understanding the phenomenon of trance in the performance of the horse dance as a religious symbols (Javanese Ideology). On the other hand, the counter hegemony of Ideology is carried out in a closed manner while still presenting the phenomenon of possession in the horse dance as a conscious act based on Javanese teachings and philosophy. Hopefully, this research can be utilized by cultural connoisseurs so as to better understand the meaning behind the symbolic phenomenon of bleakness in the art of horse dance lumping or Javanese culture in general. The results of the study may be used by clergy to better understand the religious life of Javanese people, especially among Abangan or the periphery so as to provide better spiritual assistance. In addition to cultural connoisseurs and clergy, the results of this study can also be used by researchers as discussion material in conducting further similar research, especially in analyzing, studying, and understanding Javanese culture and religion.